(untitled) (Bulletin KNOB, 2014)
The financial administration for the construction of the Utrecht Cathedral has never been thoroughly analysed in the context of its building history, even though the records of the building period of the transept and the no longer extant nave were preserved almost completely. There are relatively few accounts entries that reveal, without additional context, what materials were used for or what work was exactly done. In the end, however, there were enough clues to enable an almost complete reconstruction of the building chronology of both transept and nave of the ‘Dom’. To achieve this, we used three principles. The ‘heading method’ makes it possible to interpret ambiguous items by looking at a number of other, explicit items in the accounts. For instance, one stage in the building of the nave was reconstructed on the basis of a number of quite explicit items. Then, by ‘adding up clues’ a plausible order of construction can be established by combining a number of less explicit items. The three north chapels in the nave were dated quite accurately with this method. Finally, there is the principle of ‘confirmation’. For instance, the building period of the north chapels in the nave was confirmed in multiple ways, while that of the south chapels is confirmed by the type of stone that was used. There are many ways to obtain and apply additional information. The building sequence of the clerestory, for instance, was determined by comparing the amount of ironwork that was delivered; analysis of the amounts of mullions that were delivered helped in dating the large transept windows; and the transept’s northern fa.ade may possibly be dated by looking at the number of cornerstones of the buttresses. Studying the building administration can also offer insights into the building practices in the Middle Ages. We found that the windows of the clerestory were filled up gradually. And, contrary to current ideas, the amount of stone that was prepared at the quarry decreased significantly, after an initial increase. Another striking find is the regular involvement of master craftsmen from the city of Nijmegen in the tenders for the roof constructions. The building itself provides useful information as well for determining the chronology of the construction. For instance, the vertical sutures in the west wall of the transept suggest that this wall could only have been built after the remnants of the Romanesque transept had been demolished. In some cases, the accounts offer an explanation for irregularities in the construction. For instance, the addition of the side chapels in the nave turns out to have taken place while master builder Jacob van der Borch was still in charge. Because authors before us did not take into account the fact that building materials were sometimes stored for years before they were used, incorrect conclusions may have been drawn about the starting date of the construction of the transept’s west wall and the demolition of the Romanesque nave. Some questions still remain, however. For instance, how are we to picture the thatched roof over the middle nave that was under construction for three years from 1505 onward? And what has happened to the stone that was delivered for the flying buttresses of the nave?